2015
DOI: 10.1016/j.jconrel.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dendrimer type bio-reducible polymer as a siRNA delivery carrier for cancer therapy

Abstract: Small interfering ribonucleic acid (siRNA), 20 – 25 base pairs in length, can interfere with the expression of specific genes. Recently, many groups reported the therapeutic intervention of siRNA in various cancer cells. In this study, dendrimer type bio-reducible polymer (PAM-ABP) which was synthesized using arginine grafted bio-reducible poly(cystaminebisacrylamide-diaminohexane) (ABP) and polyamidoamine (PAMAM) was used to deliver anti-VEGF siRNA into cancer cell lines including human hepatocarcinoma (Huh-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 34 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Nam et al . evaluated an arginine-grafted, bioreducible poly(cystaminebisacrylamide-diaminohexane), called ABP, and PAMAM (PAM-ABP) for delivering anti-VEGF siRNA to various cancer types, including hepatocarcinoma, lung adenocarcinoma, and fibrosarcoma, in vitro [85]. Interestingly, their PAM-ABP dendrimer showed better gene silencing efficiency than did PEI/siRNA polyplexes.…”
Section: Polymeric Nanoparticles In Sirna Deliverymentioning
confidence: 99%
“…Nam et al . evaluated an arginine-grafted, bioreducible poly(cystaminebisacrylamide-diaminohexane), called ABP, and PAMAM (PAM-ABP) for delivering anti-VEGF siRNA to various cancer types, including hepatocarcinoma, lung adenocarcinoma, and fibrosarcoma, in vitro [85]. Interestingly, their PAM-ABP dendrimer showed better gene silencing efficiency than did PEI/siRNA polyplexes.…”
Section: Polymeric Nanoparticles In Sirna Deliverymentioning
confidence: 99%
“…3,4 Polyamidoamine (PAMAM) dendrimers are a class of synthetic polymers with well-defined structure and molecular weight. To achieve both high efficacy and low toxicity, PAMAM dendrimers of different generations were modified with cyclodextrins, 15,16 arginine, 17,18 peptides, 19 fluorous compounds, 20 polymers, 21,22 and nanomaterials. [8][9][10][11] In a pioneering study, high generation dendrimers such as generation 7 (G7) PAMAM dendrimer with a triethanolamine core efficiently induce endogenous gene silencing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown, the KSP siRNA can lead to the generation of a single star spindle promote mitotic arrest in M phase and induce apoptosis of tumor cells [14] . [15] , the body's normal proliferation of cells, there are also the expression of KSP, but its expression level was significantly lower than the malignant tissue; the body's normal differentiation and maturation of cells and tissues, such as nerve cells were not detected in the KSP expression [16] .…”
Section: Discussionmentioning
confidence: 99%